MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN AKTIVITAS MATA PELAJARAN IPAS MENGGUNAKAN MODEL PBL, NHT, DAN TGT PADA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Mutiara Sahda; Radiansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The problems identified in this study are the lack of activities and critical thinking skills possessed by students. This is because learning only flows in one direction, minimal student involvement, lack of application of learning models, and boring learning. The use of Problem Based Learning, Number Head Together, and Team Game Tournament learning strategies will help you solve this problem. This study seeks to highlight teacher activities and investigate ways to improve learning objectives, critical thinking skills, and student involvement. Three classroom action research (CAR) meetings have been carried out. Twenty-one students from class IV B at SDN Kebun Bunga 4 Banjarmasin became the subjects of the study during the second semester of the 2023–2024 academic year. The conclusion of this study explains how educators aged between 24 and 30 years work to meet the "Very Good" level. Traditionally, observations of student activity have increased from 52.38% to 90.48% when using the "Very Active" category. Critical thinking skills have traditionally increased from 47.62% to 94%. Student learning outcomes increased from 42.86% to 100% when the "Very Active" criteria were applied. Problem Based Learning, Number Head Together, and Team Games Tournament models can be used to improve student learning outcomes, teacher activities, and critical thinking skills.